Pelayanan Sosial Terhadap Lansia Pasca Pandemi Covid -19 Dalam Panti Tresna Werdha Budi Mulia 3 - Alwan Hafizh Putra Suswinarto; Almisar Hamid (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Social Services include activities and interactions that occur between social workers or caregivers and the elderly while they are in the orphanage. This research aims to determine the main problems in service, the form of service implemented as well as supporting and inhibiting factors. This research uses a library study method by utilizing literature materials in the form of books, journals and articles that are in line with the title or theme of the research. The results of the research show that the main problem in social services for the elderly is that it is difficult to manage the activities provided by social workers. The form of social services for the elderly after the Covid-19 pandemic implemented by Tresna Werdha nursing house Budi Mulia 3 includes physical changes and social changes for the elderly and provides four types of social services, namely food services, religious services, entertainment services and recreation services. In Religious Services, social workers use religious approaches such as reciting the newspaper, reading the newspaper, reading Surah Yasin.